Factors Restricting Investment Decision of Women Investors in the Indian Stock Market : An Empirical Investigation - Kumar, Prashant; Kumar, Sanjeet (Indian Journal of Research in Capital Markets, 2020)
The paper examined the factors that restrict women investors from investing in the stock market. A survey was conducted on 450 working women in selected districts of Haryana region. The present research is an exploratory study and was conducted during January – August 2019. A modified questionnaire was used to identify the factors restricting the investment decision on the basis of 23 factors, which were constructed from previous literature. Although, participation of women in all economic spheres is increasing, but women still lag behind when it comes to making investments in the stock market. Women are still bound to numerous social constraints, which have become a part of their personality and attitude. Besides these, the prevailing social norms, religious practices, and cultural values act as constraints for women from investing money and restrict their participation in the public domain. In light of this, it is contemporary to identify the problems that prevent women from investing in the stock market. It is anticipated that the present research will assist not only the women investors, but also the different financial institutions, investment consultants, stock broking houses, and other participants of the stock market in exploring the barriers that restrict the investors to invest in the stock market.